Brand Associations of BPJS Ketenagakerjaan In The Implementation of Social Security Programs - Zainudin Zainudin; Arief Dahyan Supriadi; Tarimantan Sanberto Saragih; Fadly Eka Pradana; Rendra HF Hutabarat (Eduvest - Journal of Universal Studies, 2024)
The success of the BPJS Employment social security program is strongly influenced by public perceptions and trust in this institution. Perceptions of service quality, ease of access, and program benefits shape the image of BPJS Ketenagakerjaan and determine the level of trust and loyalty of participants. This study aims to identify and analyze the brand associations of BPJS Ketenagakerjaan from the community's perspective, with a focus on participants' understanding of the social security program. This research uses a qualitative approach with data obtained through surveys and in-depth interviews. The survey involved 1,250 respondents from 11 BPJS Ketenagakerjaan Regional Offices in various parts of Indonesia, while 100 respondents were selected for interviews to explore more detailed data. The results showed three types of BPJS Ketenagakerjaan brand associations, namely true, false, and negative associations. Correct associations reflect participants' understanding of program benefits, such as health and work accident insurance. However, there are false associations due to information distortion, as well as negative associations related to complaints about complicated procedures, inadequate services, and delays in benefits. As a solution, BPJS Ketenagakerjaan is expected to improve service quality, expand socialization, develop innovation, implement digitalization, and build collaboration to create positive brand associations. These steps aim to support the institution's image and strengthen public trust in the social security program